Gaze-based assistive technology in daily activities in children with severe physical impairments–An intervention study - Borgestig, M.; Sandqvist, J.; Ahlsten, G.; Falkmer, Torbjorn; Hemmingsson, H. (Informa Healthcare, 2017)
Objective: To establish the impact of a gaze-based assistive technology (AT) intervention on activity repertoire, autonomous use, and goal attainment in children with severe physical impairments, and to examine parents’ satisfaction with the gaze-based AT and with services related to the gaze-based AT intervention. Methods: Non-experimental multiple case study with before, after, and follow-up design. Ten children with severe physical impairments without speaking ability (aged 1–15 years) participated in gaze-based AT intervention for 9–10 months, during which period the gaze-based AT was implemented in daily activities. Results: Repertoire of computer activities increased for seven children. All children had sustained usage of gaze-based AT in daily activities at follow-up, all had attained goals, and parents’ satisfaction with the AT and with services was high. Discussion: The gaze-based AT intervention was effective in guiding parents and teachers to continue supporting the children to perform activities with the AT after the intervention program.